Gut microbiota-mediated pain sensitization: mechanisms and therapeutic implications - Zhao, Minghe; Zhang, Ling; Liu, Zhihui (Frontiers in Pain Research, 2025)
Emerging evidence has illuminated the pivotal role of gut microbiota in modulating pain sensitivity through bidirectional gut-brain interactions. Current research demonstrates that gut microbial communities significantly influence pain perception by regulating both central and peripheral sensitization mechanisms across various pain modalities. This review synthesizes current knowledge on the mechanisms underlying gut microbiota-mediated pain sensitization, encompassing: (1) cross-talk within the microbiome-gut-brain axis, (2) regulatory effects of microbial metabolites on central and peripheral sensitization pathways, and (3) bioactive compounds derived from gut microbiota that participate in pain modulation. Furthermore, we systematically evaluate the therapeutic potential of microbiota-targeted interventions including probiotic supplementation, fecal microbiota transplantation, and dietary modifications in pain management. To advance this promising field, future investigations should prioritize three key directions: establishing causal relationships through rigorous verification, accelerating clinical translation of preclinical findings, and developing personalized microbial-based therapeutic strategies.